Unveiling the influences of P fertilization on bioactive compounds and antioxidant activity in grains of four sorghum cultivars. - Mohammed Elsafy; Nouralhuda A J Tia; Khitma A Sir Elkhatim; Mazahir H Othman; Amro B Hassan; Mahbubjon Rahmatov; Tilal Sayed Abdelhalim (PLoS ONE)
Backgrounds Phosphorus is a critical nutrient in agriculture, influencing plant growth and nutritional quality. Objectives This study, uniquely designed to investigate the effects of phosphorus (P) fertilization levels, sorghum cultivars, and growing locations on phytochemical content and antioxidant activity in sorghum grains, employed four sorghum cultivars (Hakeka, P954063, Tabat, and Tetron) grown under three P levels (0P, 1P, 2P) in two locations (Gezira and White Nile) in Sudan. Methods In this study, four sorghum cultivars were grown in two distinct locations in Sudan, employing a split-plot design with three (P) fertilization levels. P was applied as triple super phosphate directly with the seeds, and additional fertilization included urea applied in two split doses. At physiological maturity, representative sorghum panicles were harvested, processed, and analyzed for bioactive compounds and antioxidant activities using standard extraction and quantification techniques such as Folin-Ciocalteu for phenolics and colorimetric flavonoid assays. Antioxidant activities were assessed through various assays, including DPPH and FRAP. Statistical analyses were performed using a three-way ANOVA to examine the effects of cultivar, P level, and location on the measured parameters, supplemented by multivariate analysis to further elucidate the interactions between these factors. Results Significant interactions (p<0.001) were observed among cultivars, P levels, and locations for total phenolic content (TPC), total flavonoid content (TFC), carotenoids, tannins, and various antioxidant activity measures (DPPH, FRAP, ABTS, TRP, H2O2). P fertilization significantly increased all measured phytochemicals and antioxidant activities compared to non-treated cultivars, except for H2O2, which decreased with P application. Among cultivars, Hakeka consistently exhibited the highest TFC, carotenoid content, and antioxidant activities (DPPH, FRAP, TRP, ABTS), particularly at the 2P level. P954063 showed the highest TPC and tannin concentrations. Tetron generally had the lowest phytochemical and antioxidant levels. White Nile showed higher TPC, carotenoids, DPPH, FRAP, TRP, and ABTS levels, while Gezira had higher TFC, tannins, and H2O2 concentrations. The impact of phosphorus fertilization often varies between locations. Strong positive correlations were found between TPC and all antioxidant assays (r = 0.68-0.90) and total carotenoids and antioxidant activities (r = 0.73-0.93). Conclusions This study recommended cultivating the Tabat variety with 2P doses in Gezira. In addition, the Hakeka cultivar showed the highest increases in total flavonoid content, carotenoids, and antioxidant activities, particularly under the highest P level (2P). The findings highlight that P plays a critical role in enhancing sorghum's nutritional and health-promoting qualities, which are essential for leveraging this staple crop for food and nutrition security strategies in semi-arid regions.